2000
DOI: 10.1080/10807030091124581
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Incorporating Information on Chemical Availability in Soils into Risk Assessment and Risk-Based Decision Making, Prepared by: The New England Environmentally Acceptable Endpoints Workgroup

Abstract: A regional workgroup comprised of individuals from regulatory agencies, universities, and consulting companies was formed to develop an approach for incorporating information on chemical availability in soils into risk assessment and riskbased decision making. The approach consists of the following decision framework for including information on chemical availability: (1) Determine the usefulness of incorporating information on bioavailability; (2) Identify information needs from a conceptual model of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Taken together, these observations demonstrate that caution should be exercised when applying BSAFs across sites with greatly different PCB concentrations. Similar cautions have been raised in regards to the application of BSAFs from one site to another since there are potential differences in soil and sediment characteristics that may affect bioavailability (32).…”
Section: Ranges Of Pcb and Teq Concentrations In Terrestrial Foodmentioning
confidence: 99%
“…Taken together, these observations demonstrate that caution should be exercised when applying BSAFs across sites with greatly different PCB concentrations. Similar cautions have been raised in regards to the application of BSAFs from one site to another since there are potential differences in soil and sediment characteristics that may affect bioavailability (32).…”
Section: Ranges Of Pcb and Teq Concentrations In Terrestrial Foodmentioning
confidence: 99%
“…This so-called linear sorbed fraction has been shown to relate to biodegradation [5,6] and * To whom correspondence may be addressed (d.thulscher@riza.rws.minvenw.nl). also to uptake by organisms [7][8][9][10][11][12]. Since bioavailability seems to be strongly related to the way chemicals are sorbed in sediments and soils, a short overview of the recent insights in sorption mechanisms is presented below.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has indicated that it is not the total concentration of a chemical in sediment or soil that is relevant for its bioavailability, but the fraction that can desorb to the surrounding (pore) water within a few hours. This so‐called linear sorbed fraction has been shown to relate to biodegradation [5,6] and also to uptake by organisms [7–12]. Since bioavailability seems to be strongly related to the way chemicals are sorbed in sediments and soils, a short overview of the recent insights in sorption mechanisms is presented below.…”
Section: Introductionmentioning
confidence: 99%